Information communication technologies as a support mechanism for learners experiencing reading difficulties - Mphahlele, Ramashego Shila Shorty (2014)
Reading difficulties are of concern worldwide, as evidenced by a number of studies, including the Association for the Development of Education in Africa (ADEA), the Centre for Evaluation & Assessment (CEA), and Progress in International Reading Literacy (PIRLS). In South Africa’s, Gauteng Province, in which this study was conducted, the Department of Education (DoE) launched campaigns, such as Foundations for Learning (FFL) and Annual National Assessment (ANA) to address this problem. The purpose of this study was to explore, explain and describe the use of Information Communication Technologies (ICTs) to support learners experiencing reading difficulties in two public primary schools. The study was influenced by Vygotsky’s socio-cultural theory of human learning that describes it as a social process and the origination of human intelligence in society or culture. It comprised skills, assumptions and practices that the researcher used when moving from paradigm to the empirical world. A qualitative approach was used to gain first-hand holistic understanding of the use of ICTs to support learners experiencing reading difficulties, with data collected using focus group interviews, individual interviews and observations. Participants were 18 members of the School Based Support Team (SBST) and two Learning Support Educators (LSEs) of the two selected primary schools. The use of ICTs as a support mechanism was explored, with a detailed view presented on the use of ICTs by the teachers during teaching and learning activities and how they supported learners experiencing reading difficulties. From the research findings, factors affecting learners experiencing reading difficulties were identified, including lack of resources (specifically ICTS) and lack of guidelines on identifying and providing support to the learners experiencing reading difficulties. Based on the findings, conclusions and recommendations were made and the researcher developed guidelines which could be used by teachers to provide ICTs support for learners with reading difficulties. === Educational Studies